Primary Amelanotic Rhabdoid Melanoma: A Case Report with Review of the Literature - Takahide Kaneko; Ayumi Korekawa; Eijiro Akasaka; Daiki Rokunohe; Hajime Nakano; Daisuke Sawamura (Karger Publishers, 2015)
Primary rhabdoid melanoma (PRM) is a rare variant of melanoma. Herein, we describe a case of primary amelanotic rhabdoid melanoma and review the clinicopathological features of previously reported cases of PRMs. A 63-year-old Japanese man presented with a nonpigmented red granular tumor without peripheral pigmented macules on the left heel measuring 21 × 18 mm in size. Light microscopic examination revealed a tumor mass composed entirely of polygonal neoplastic cells resembling pulmonary alveoli. Tumor cells were also discohesive with bizarre nuclei, prominent nucleoli and large hyaline cytoplasmic inclusions. No melanin pigment was present. Tumor cells were strongly and diffusely positive for S-100, MART-1, HMB-45 and vimentin, while negative for desmin, αSMA and synaptophysin. According to previous reviews, PRM tends to be amelanotic and nodular. S-100 protein and vimentin stained in all cases contrary to low stainability for HMB-45, which was, by contrast, positive in our case. Prognosis of PRM remains controversial due to the very rare occurrence of this tumor and the small number of confirmed cases that have been reported. Recognition of this rare entity is important in clinical practice even for skillful dermatologists to avoid misdiagnosis with the other tumors and to determinate the subsequent treatment principles.